Effect of share collateralization by directors/supervisors on control rights, risk, and performance: application to the Taiwan market. Issue 3 (3rd July 2019) - Lee, Kuo-Jung; Lu, Su-Lien; Lin, Ching-Yi
Abstract: Share collateral is a popular and no restriction process in many capital markets. The directors/supervisors can pledge their shares as collateral to the lender for funding in capital markets. There are many purposes for directors/supervisors to collateral their shares, such as the demand for liquidity. Thus, this study investigates the effect of share collateralization by directors/supervisors in Taiwan. Further, this study explores the effect of directors'/supervisors' actual shareholdings. The sample is divided into two classes, conventional and nonconventional industries, and the sample period spans 11 years, from 2003 to 2013. The panel data regression model is used to determine whether the hypothesis of this paper is supported. The empirical results show that an increase in shares collateralized by directors/supervisors resulted in the widening of deviation between cash flow rights and ownership control rights. However, an increase in shares collateralized by directors/supervisors would not result in the widening of deviation between cash flow rights and board control seat rights. Further, the higher the ratio of director/supervisor share collateralization, the greater firm's risk. Finally, directors'/supervisors' actual shareholdings have a positive correlation on performance.